Analysis of The Influence of Lending Rates, Bad Loans, and Liquidity Ratios on Credit Disbursement - Maulana, Prisatia Windu; Hardiwinoto, Hardiwinoto; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
The existence of the financial sector in a country's economy plays a crucial role in encouraging economic growth. Almost all financial sectors are directly related to banking services. Fundraising and distribution activities are the main activities of banking. Focusing on credit is the nature of the banking business as an intermediary between surplus and deficit units and the main source of bank funds comes from the community so morally it must be returned to the community in the form of credit (Siamat, 2005). The type of research used by the researcher is a quantitative approach with a causal associative method. In this chapter to analyze the influence of Loan Interest Rates, Bad Loans and Liquidity Ratios on Credit Distribution at SOE banks and Bank Jateng in the city of Semarang. The research sample is five banking companies, which are determined by the purposive sampling method. The type of data used is secondary data in the form of annual banking reports for the 2017-2023 period. The data analysis technique uses multiple linear regression analysis with the help of the SPSS version 25.0 program. The results of this study show that: Loan interest rates and Liquidity Ratio have a significant positive effect on credit disbursement while Bad Loans have no effect on credit disbursement.